Applying phenomenological method to educational research - Nguyễn Thị Mỹ Lệ , (Journal of Technical Education Science, 2012)
Phenomenology has been discussed in philosophy with so much interest for a long time. This article, however, does not concern with presenting phenomenology as philosophers' viewpoints found in philosophy books, but talks about using phenomenological method in educational researches. The writing also tries to highlight several advantages of the method. It consists of three parts: the first shows the origin and concept of phenomenology; the second describes how to take up phenomenology in education; and the last puts forth some proposals for using phenomenology in educational researches